2018
DOI: 10.17511/ijpr.2018.i05.07
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D supplementation in children with severe acute malnutrition in a nutritional rehabilitation centre: a randomized controlled trial

Abstract: Background: According to World Health Organization (2013) approximately 35% of the under-fivemortalities are due to nutrition related factors & 4.4% of deaths are due to severe wasting. It has been found that Vitamin D levels are low in children with malnourished and very sick children. Even the prevalence of vitamin D deficiency is very high in Indian subcontinent. In WHO recommendations for the management of severe acute malnutrition there is no role of vitamin D supplementation. Objective: To study the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 9 publications
3
5
0
Order By: Relevance
“…Other complications are severe anemia, different stages of dermatitis, etc. Maurya et al, showed Acute gastroenteritis and pneumonia were the most common complication affecting 33.3% and 12.5% children [18]. In our study 46% children were exclusively breast fed, only 20% children had timely initiation of complimentary feeding.…”
Section: Discussionsupporting
confidence: 41%
See 3 more Smart Citations
“…Other complications are severe anemia, different stages of dermatitis, etc. Maurya et al, showed Acute gastroenteritis and pneumonia were the most common complication affecting 33.3% and 12.5% children [18]. In our study 46% children were exclusively breast fed, only 20% children had timely initiation of complimentary feeding.…”
Section: Discussionsupporting
confidence: 41%
“…The difference was not statistically significant (p>0.05) among groups. Maurya et al, (2018) observed a slight male preponderance Male: Female 1.91:1 in control group and 1.69:1 in case group [18]. Nahida et al, (2017) study found male preponderance in severe acute malnourished children with 56.7% male and 43.3% female [20].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This causes a tendency to decrease serum vitamin D levels due to impaired synthesis. 9 Research on the relationship between serum vitamin D levels in malnourished children in Indonesia has not been conducted. In a state of malnutrition, there is a decrease in the concentration of vitamin D receptors.…”
Section: Introductionmentioning
confidence: 99%